Public Service Innovation in Issuance of Building Permits in Sidoarjo Regency - Malihatul Fuadah; Ismi Dwi Astuti Nurhaeni; Sri Yuliani (Iapa Proceedings Conference, 2021)
The innovation of public services provided by the Investment and One Stop Service Office provides many benefits for people who use the services and services of the relevant agencies. This innovation also helps a lot in terms of issuing building permits which are one of the most needed public services by the community, where in its implementation requires accuracy and speed in managing and issuing building permits so that buildings used for business get legal. The purpose of the launch of SIPPADU has been stated in the Regulation of the Regent of Sidoarjo Number 8 of 2017 concerning the Application of Information Technology in Integrated Services. The type of research used is descriptive research with a qualitative approach. The focus in this research is how public service innovations in overcoming delays in the issuance of IMB files through the Integrated Licensing Service Information System program by the Investment Office and One Stop Integrated Service of Sidoarjo Regency which includes forms of innovation, processes and cycles of innovation as well as the diffusion of innovations at the Investment Office. and One Stop Services in Sidoarjo Regency. Based on the results of the research above, it can be concluded that technology-based innovations made by the Office of Investment and One Stop Integrated Services, namely the SIPPADU application, have helped the operation of licensing services at the agency. the service is to upgrade this SIPPADU innovation in the future so that things don't happen such as unstable networks, applications or websites that can't be accessed because the server is down. As well as providing more direction to existing Human Resources to understand more about SIPPADU. Suggestions for the public is to add more information about the SIPPADU application which can be accessed through the website of the Sidoarjo Regency Investment and One Stop Integrated Service website.